To solve the equation 1/3 * (6x - 9) = -33, we can begin by distributing the 1/3 to the terms inside the parentheses:
(1/3) * 6x - (1/3) * 9 = -33
Simplifying, we have:
2x - 3 = -33
Next, we can add 3 to both sides of the equation to isolate the variable:
2x - 3 + 3 = -33 + 3
Simplifying further, we get:
2x = -30
Finally, we can divide both sides of the equation by 2 to solve for x:
(2x) / 2 = -30 / 2
x = -15
Therefore, the solution is x = -15.
Solve for x.
(1 point)
x = - 30
x = - 15
x = - 22
x = - 19
1/3 * (6x - 9) = - 33
page 2 of 2
1 answer